Factors associated with COVID-19 mortality in municipalities in the state of São Paulo (Brazil): an ecological study - Souza, Rafaela Caroline de [UNESP]; Almeida, Ettore Rafael Mai [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Miot, Hélio Amante [UNESP] (FapUNIFESP (SciELO), 2022)
Background: The mortality rate of coronavirus disease (COVID-19) in the state of São Paulo is highly heterogeneous. This study investigated geographic, economic, social, and health-related factors associated with this discrepancy. Methods: An ecological study compared COVID-19 mortality rates according to geographic, economic, social, and health-related variables during initial infection of 2.5% of the population in municipalities with more than 30,000 inhabitants. Results: Mortality was positively associated with demographic density and social inequality (Gini index), and inversely associated with HDI income and longevity of these municipalities, accounting for 33.2% of the variation in mortality. Conclusions: Social determinants influenced COVID-19 outcomes.
Keywords: COVID-19; Ecological studies; Health inequality; Human development index; Mortality; SARS-CoV-2; Social inequality